Efektifnya Video Belajar Berbasis Game di Pusat Budaya Bali Tentang Karakter Toleransi Anak-Anak di Daerah Aliran Sungai - Antara, Putu Aditya; Dewi, Ni Putu Sinta; I Wayan Ardana (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Tolerance is a way of life that includes words, acts, and conduct that demonstrate a regard for other people. Tolerance requires a broad knowledge base, an open mindset, freedom of opinion, and faith. This study is quasi-experimental in nature, using a pretest-posttest control group design. Indicators of attitude integrated tolerance with video media, core video content culture Bali, and enrichment attitude tolerance related culture loaded Bali in the video are used to assess efficacy in the use of learning videos. Wilcoxon's non-parametric statistical paradigm was used to examine the data. A significance test is used to interpret the data. There was a considerable effect and development in the abilities and skills of teachers teaching in the Banyumala watershed before and after they participated in training to create instructional films based on Balinese cultural centers. This is backed up with strategies that are straightforward and easy for instructors to grasp. The average score of teachers teaching in kindergartens surrounding the DAS Banyumala river basin is greater than the average score of teachers teaching in Sukasada sub-district and elsewhere. As a result, we anticipate that teachers' skills in creating learning films will increase and that they will be able to apply Balinese cultural centers in early childhood education through various forms of training activities.